The Benefits of Interactive Media Websites Through Google Sites on Learning Outcomes of Elementary School Students - Halimatusyadiah, Hema; Disman, Disman (Faculty of Humanities, Universitas Jenderal Soedirman, 2023)
The application of technology in education will improve teachers’ ability to convey material to students, make it easier for students to understand the material presented, and make time more effective and efficient. Advances in computers are also closely related to the world of education. Most schools also include computers as a compulsory subject. Technology's role in education is growing rapidly, and the need for technology is indispensable in the current era of globalization. By utilizing recent technological developments, the aims of this research are (1) to develop website-based learning media; (2) to analyze the differences in learning outcomes between students who use websites and conventional media. Researchers use a Google Sites application to support the development of web-based learning media. Teaching staff can use Google Sites to carry out various learning activities. The stages of this research method are experimental research with a posttest only control group design. The subjects of this study were students of class IV A and B at SDN 2 Karangsari—intake of research class through random sampling technique. Activities in data analysis include data processing and statistical analysis. The conclusion of this study is that the learning model through website learning media can generally motivate students to improve learning outcomes. Students gave a positive response to the implementation of the website learning model.